INCLUSIVE HUMAN RESOURCE DEVELOPMENT - THE FRUIT OF INCLUSIVE GROWTH IN INDIA - SHARMA, JYOTI KUMARI (International Journal of Research -GRANTHAALAYAH, 2021)
Under the a national consciousness, the national integration refers to process which is to bring all the different race, religions, cultures and linguistic groups together into one single nation. It aims at removing socio-cultural, economic inequality and strengthening unity by giving human dignity to all citizens without any discrimination. We know that India represents a paradoxical dynamic economy, among high economic processes followed by a rise in indifference, poverty, and regional imbalances. Under this, it was found that the development of abilities and skills of human beings under human resource development enhances the use of physical capitals’ successfully, positively, and progressively. It is done by educating, providing better health facilities, and developing skills of the country’s citizens, helps them to add to productivity, increasing the national wealth of the country. Accordingly, when Human Resource Development is more inclusive, respect and understanding grow. Further, inclusive Human Resource Development strategy increases the productivity of the country, with the development of productive capacity, physical capability, and mental capability of its human resources, which leads to all-round economic development and growth of the country. In this way, through my study-made in this paper, I look forward to describe and explain the process of reducing all kinds of socio-economic exclusion from India by implementing the inclusive growth strategy that helps to reduce poverty with the help of the income (wages) earned from the jobs of each citizen, guaranteeing food security, education, health, employment, etc. facilities for all. Thus, inclusive Human Resource Development strategy can reduce and remove inequality from India, accompanied by social welfare with stability.